Anaesthesia for the patient undergoing Hepatectomy - Shakya, Bigen Man (Journal of Society of Anesthesiologists of Nepal, 2015)
A 41 year old lady was planned for left hepatectomy for Intrahepatic Cholangiocarcinoma. This article describes the case and perioperative concerns during hepatectomy. Hepatectomy is a challenging procedure both for surgeons and anaesthesiologist. Better understandings of physiology and advancements in both the fields have markedly reduced the mortality related to hepatectomy. The major concern is the blood loss during the resection of tumor. Blood loss is minimized by multi - modal perioperative techniques. Pringle maneuver is used by surgeons to minimize blood loss during resection but have significant hemodynamic changes. The central venous pressure should be kept below 5 cm of H2O particularly during resection to minimize blood loss. The use of epidural for postoperative analgesia is controversial. Postoperative hepatic failure occurs in 3 % of cases. A good postoperative care with monitoring on relevant parameters is needed for better outcome. Journal of Society of Anesthesiologists 2014 1(1): 49-50